2022
DOI: 10.3390/ijerph192113756
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Assessment of Indoor Environmental Conditions in Educational Building Using Building Information Modelling Methodology

Abstract: Managing indoor environmental quality (IEQ) is a challenge in educational buildings in the wake of the COVID-19 pandemic. Adequate indoor air quality is essential to ensure that indoor spaces are safe for students and teachers. In fact, poor IEQ can affect academic performance and student comfort. This study proposes a framework for integrating occupants’ feedback into the building information modelling (BIM) methodology to assess indoor environmental conditions (thermal, acoustic and lighting) and the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…2.2 Use of occupant feedback in building information modelling-enabled facility management BIM is a promising platform for representing occupant feedback in 3 D models, which allows for visual representation of occupant feedback, querying, and detecting problems and related components in a rapid way. Several studies represented occupant satisfaction rate or the number of issues in colour coding in the BIM model (Hua et al, 2014;Göçer et al, 2015;Patlakas et al, 2017;Pin et al, 2018;Alavi et al, 2021;Aguilar et al, 2022). Other studies collected thermal comfort-related data (e.g.…”
Section: Literature Review 21 Occupant Feedback Collectionmentioning
confidence: 99%
“…2.2 Use of occupant feedback in building information modelling-enabled facility management BIM is a promising platform for representing occupant feedback in 3 D models, which allows for visual representation of occupant feedback, querying, and detecting problems and related components in a rapid way. Several studies represented occupant satisfaction rate or the number of issues in colour coding in the BIM model (Hua et al, 2014;Göçer et al, 2015;Patlakas et al, 2017;Pin et al, 2018;Alavi et al, 2021;Aguilar et al, 2022). Other studies collected thermal comfort-related data (e.g.…”
Section: Literature Review 21 Occupant Feedback Collectionmentioning
confidence: 99%
“…Therefore, it cannot be assumed that the thermal comfort requirements of university students are the same as those of office workers [159,281]. Several authors also observed that university students preferred a warmer indoor environment during colder seasons when classrooms were naturally ventilated [240,241]. It was also found that the range of thermal dissatisfaction was wider than that of cold dissatisfaction.…”
Section: Climatic Zone Seasons and Operationmentioning
confidence: 99%
“…The IEQ can be described as a combination of indoor thermal parameters, indoor air pollutant parameters, as well as lighting, acoustic, and spatial factors [18,19]. Among these parameters, indoor thermal parameters [20] and air quality-related parameters [21] are typically applied to monitor the variation of IEQ inside buildings. In particular, comprehensive IEQ monitor systems have recently been developed for inspecting variations in multiple indoor environmental parameters.…”
Section: Introductionmentioning
confidence: 99%